(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Fluoroscopy or C-arm imaging is frequently used in Orthopaedic surgery and Orthopaedic surgeons are exposed to excessive ionizing radiation and they can be considered as high risk health care workers for occupational radiation exposure.1 This radiation exposure is an additional occupational hazard besides other risks of surgery because Orthopaedic surgeons are not classified radiation workers.2 Unfortunately majority of Orthopaedic surgeons lack the awareness and are less sensitive to radiation hazards because the effects of excessive radiation are manifested overs months or years and are not immediately manifested or observed.3 The C-arm fluoroscopy emits x-ray radiation which produces free radicals due to ionizing effects which lead to direct DNA damage, cell death and biological damage.4